Academic, Technical and Skills, Adaptation and Social Abilities towards Student Achievement - Mochamad Rozikin; Septiana, Vena; Sujarwoto (LPPM Undiksha, 2024)
There is a need to understand the factors that influence student achievement in education, especially how to analyze the relationship between interest, motivation and learning style with various other factors such as academic, technical, skills, adaptation and social abilities that affect student achievement. The main objective of this study is to analyze academic, technical skills, adaptation, and social abilities about student achievement, as well as the role of interest, motivation, and learning style in determining educational outcomes. This type of research is quantitative with a Partial Least Squares (PLS) methodology approach, using SmartPLS 3.0 software for data analysis. The subjects of the study consisted of a population of 1,241 vocational high school students from grades X to XII. Sampling was done using the proportional stratified random sampling technique with the Taro Yamana formula at a significance level of 5%, and a sample of 294 students was obtained. The structural model shows a significant influence of exogenous variables (academic, technical, social, and adaptation abilities) on interest and motivation (R-square equals 0.774) and learning style (R-square equals 0.822). Although some hypotheses did not reach statistical significance, seven others showed significant effects. These findings emphasize the role of interests, motivation, and learning styles as mediators and suggest the need for more effective educational policies to improve academic outcomes.